2020
DOI: 10.1038/s41598-020-71422-y
|View full text |Cite|
|
Sign up to set email alerts
|

Ethnic variation of oral microbiota in children

Abstract: Despite widely used preventive measures such as sealant programs to control caries prevalence, disparities are seen among ethnic groups. Supragingival plaque harbors hundreds of bacterial species, playing a significant role in oral health and disease. It is unknown whether the ethnic variation influences the supragingival microbiota in children. In our study, variations in microbiota of the supragingival plaque was investigated from 96 children between 6 and 11 years old in four ethnic groups (African American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…A number of studies have examined oral microbial communities of human hosts of different ethnic or environmental origin [36] , [37] , [45] [47] . However, comparisons with our study are not always straightforward, since there are differences in the area of sampling (saliva, tonsils, supragingival and subgingival dental plaque) and the age of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have examined oral microbial communities of human hosts of different ethnic or environmental origin [36] , [37] , [45] [47] . However, comparisons with our study are not always straightforward, since there are differences in the area of sampling (saliva, tonsils, supragingival and subgingival dental plaque) and the age of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparisons with our study are not always straightforward, since there are differences in the area of sampling (saliva, tonsils, supragingival and subgingival dental plaque) and the age of subjects. Premaraj et al identified seven ethnic group-specific bacterial taxa among supragingival plaque of children between 6 and 11 years old in four ethnic groups (African American, Burmese, Caucasian, and Hispanic) and found that the microbial alpha diversity of supragingival microbiota significantly differed between ethnic groups [45] . Mason et al found that the subgingival microbial fingerprint could successfully discriminate between people four major ethnicities in the United States: non-Hispanic blacks, non-Hispanic whites, Chinese, and Latinos (over 18 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding geographical factors, former studies reported that adult populations from different continental regions or even countries had microbial variations in saliva (Nasidze et al, 2009;Li et al, 2014), and supragingival microbiota differed among ethnic groups (i.e., African American, Burmese, Caucasian, and Hispanic) in children from the same geographic location (i.e., Burma) (Premaraj et al, 2020). Those studies showed the importance of understanding the bacterial community across geography.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on diversity and function of healthy human microbiomes started in 2012 by the Human Microbiome Project Consortium [ 10 ]. The gut and oral microbiota can be a signature of ethnicity [ 11 , 12 ]. A change of gut microbiota directly correlates with diet and various diseases [ 13 ].…”
Section: Global Trends Of Metagenome Studiesmentioning
confidence: 99%